Are dream emotions shifted towards more negativity compared to waking-life emotions?: an empirical study - Schredl, Michael (International journal of dream research, 2025)
Emotions are an integral part of the dream experience and research has focused on the interplay between waking-life emotions and dreams emotions. Previous studies indicate a so-called negativity bias, that is, the emotional tone of dreams is on average lower than the average waking life mood. Overall, 83 participants completed a questionnaire and were then divided into two subgroups keeping different versions of dream diaries. The findings support the notion of a positivity bias regarding the retrospective measurement of overall emotional quality in waking life and a negativity bias regarding dream emotions. In addition, there is a medium sized correlation between the two domains, supporting the notion of an emotional continuity between waking and dreaming. Future research can use experience sampling methods in conjunction with dream diaries to study the interaction between waking-life emotions and dream emotions more closely.
Gesehen am 08.10.2025